2018
DOI: 10.1016/j.eurpolymj.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerized bioceramics for drug delivery: Do surface changes alter biological behaviour?

Abstract: One of the treatments for recurrent or complicated osteomyelitis is by local antibiotherapy mediated by suitable bone grafts. β-Tricalcium Phosphate (β-TCP) bioceramic is a resorbable bone graft. Its microporosity allows for incorporation of drugs, but a too fast release is often obtained. Complex strategies have been explored to obtain controlled drug release. In this work, plasma polymerization of a biocompatible polymer was investigated on β-TCP. Polyethyleneglycol (PEG)-like polymer coatings of different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, extensive surface characterization is required to elucidate the surface properties and chemistry of the resulting plasma-polymerized coatings and to correlate these to the applied parameters in the plasma process. Over the years, the plasma polymerization process of a wide range of precursors has been extensively studied, including carboxylic acids, alcohols, amines, siloxanes, and ethers. In contrast to these types of monomers, the use of amide-based precursors for plasma deposition has only been reported in a few studies. Pan et al and Chu et al reported the plasma-assisted synthesis of thermosensitive films based on, respectively, N -isopropylacrylamide (NIPAM) and N , N- diethylacrylamide (DEAM). ,, Cheng et al reported temperature-dependent protein adsorption on plasma coatings based on NIPAM, and Griesser et al observed good cell attachment and growth on films fabricated by plasma polymerization of N , N -dimethylformamide (DMF), N , N -dimethylacetamide (DMA), and N , N -dimethylpropionamide (DMP). , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive surface characterization is required to elucidate the surface properties and chemistry of the resulting plasma-polymerized coatings and to correlate these to the applied parameters in the plasma process. Over the years, the plasma polymerization process of a wide range of precursors has been extensively studied, including carboxylic acids, alcohols, amines, siloxanes, and ethers. In contrast to these types of monomers, the use of amide-based precursors for plasma deposition has only been reported in a few studies. Pan et al and Chu et al reported the plasma-assisted synthesis of thermosensitive films based on, respectively, N -isopropylacrylamide (NIPAM) and N , N- diethylacrylamide (DEAM). ,, Cheng et al reported temperature-dependent protein adsorption on plasma coatings based on NIPAM, and Griesser et al observed good cell attachment and growth on films fabricated by plasma polymerization of N , N -dimethylformamide (DMF), N , N -dimethylacetamide (DMA), and N , N -dimethylpropionamide (DMP). , …”
Section: Introductionmentioning
confidence: 99%
“…According to the previous study, it was reported that the hydrophobic state of implant biomaterial resulting from the "aging effect" can change to the hydrophilic surface through the ultraviolet (UV) light treatment of aged implants [12,13]. Recently, a number of studies reported that atmospheric pressure plasma (APP) surface treatment can turn a surface hydrophilic and even enhance biocompatibility and cell responses [1,16,17,33,34]. Thus, we expected that the APP treatment can modify the surface of bone graft material by improving surface energy and assumed that such surface treatment can reactivate the expired bone graft material.…”
Section: Discussionmentioning
confidence: 99%